Prices behind electro-mobility: Contestation around and beyond price determination and setting in the lithium global production network and extraction in Chile - Luisa Leisenheimer (Südwind-Verlag, 2022)
Against the background of political and academic debates around strategies to slow down global warming, the shift to electro-mobility is broadly perceived as a key strategy, particular in the Global North but also countries such as China. There are high expectations in electric vehicles (EVs) and the prevailing technology of lithium-ion batteries which demand a rapid increase of its main component lithium. A growing body of literature thereby focuses on the problematic socio-ecological impacts of lithium extraction. However, despite the current peak in lithium prices, limited attention has been put on the role of prices and pricing in research and policy circles around green extractivism. In contrast to the premise of prices simply being an output of supply and demand in abstract markets - an assumption propagated by neoclassical thinking - prices and price determination must be seen as politically, socially, and culturally embedded. Price determination procedures are contested processes taking place in an environment of competition and are (re-)producing status, power and trust that have distributional impacts. Based on 22 interviews with lithium sector stakeholders and experts in Europe and Chile, one of the main lithium producing countries worldwide, this thesis assesses the contestation around and beyond price determination and setting processes in lithium extraction in Chile and the lithium global production network. Currently, price determination in the lithium market is rather opaque and there is not one world price to be used throughout the industry. These opaque contracts and prices stabilise the power of producers in the production network of lithium. At the same time powerful price determination institutions like the London Metal Exchange (LME) and Price Reporting Agencies (PRAs) follow practices that lack transparency, and often pursue rather short-term strategies instead of considering long-term risks and costs like ecological degradation. How and by whom (lithium) prices are determined has important distributional outcomes as this process includes social and environmental concerns and questions of representation and inclusion in decision-making processes. The complex political economy in Chile, social injustices and fights over territories furthermore structure the socio-cultural realities of lithium extraction and influences global trade patterns. The control of lithium extraction by only two companies, strengthens their position in price determination processes on a global level and together with a political system in Chile where almost all power originates from the centre weakens the opportunities of alternative production systems and critical voices towards the model of green exractivism. Generally, the high demand for lithium induced by a certain narrative about a socio-ecological transformation can foster the unsustainable use of lithium. – – Vor dem Hintergrund politischer und akademischer Debatten um Strategien im Kampf gegen die Klimakrise, betrachten insbesondere Länder im Globalen Norden aber auch Länder wie China den Übergang zur Elektromobilität als essenziell. Besonders hohe Erwartungen gilt dabei den Elektroautos und der vorherrschenden Technologie von Lithium-Ionen-Batterien, die einen raschen Anstieg ihres Hauptbestandteils Lithium erfordert. Autor*innen und Forscher*innen befassen sich momentan vor allem mit den problematischen sozio-ökologischen Auswirkungen des Lithium-Abbaus. Trotz der enorm hohen Lithiumpreise, wurde jedoch der Rolle von Preisen und der Preisgestaltung bis heute nur wenig Aufmerksamkeit geschenkt - weniger noch im Zusammenhang mit dem Konzept des grünen Extraktivismus. Entgegen der von der Neoklassik propagierten Prämisse, dass Preise lediglich Ergebnis von Angebot und Nachfrage seien, müssen Preise und die Preissetzung als politisch, sozial und kulturell verankert betrachtet werden. Preisfindungsprozesse sind also umkämpfte Prozesse, welche Status und Macht (re-)produzieren und damit direkt mit der Verteilung von Wohlstand verbunden sind. Auf der Grundlage von 22 Interviews mit Interessensvertretungen und Expert*innen des Lithiumsektors in Europa und in Chile, einem der wichtigsten lithiumproduzierenden Länder, setzt sich diese Arbeit mit umkämpften Prozessen um Preissetzung in globalen Produktionsnetzwerken von Lithium mit Fokus auf Chile auseinander. Derzeit ist die Preisbildung im Lithiumsektor enorm intransparent und es gibt keinen einheitlichen Weltmarktpreis. Die Arbeit zeigt, dass intransparente Verträge und Preise die Macht von Lithiumproduzent*innen stärken. Gleichzeitig verfolgen mächtige Preisfestsetzungsinstitutionen wie die Londoner Metallbörse (LME) und Preisberichtsagenturen (PRAs) bestimmte Interessen und intransparente Praktiken, welche die langfristigen Risiken und Kosten von Ressourcenextraktion wie die ökologische Zerstörung ignorieren. Wie und von wem (Lithium-)Preise festgelegt werden, hat wichtige Auswirkungen auf die Verteilung, da dieser Prozess soziale und ökologische Belange sowie Fragen der Inklusion in Entscheidungsprozesse enthält. Die komplexe politische Ökonomie in Chile, soziale Ungerechtigkeiten und Kämpfe um Territorien strukturieren darüber hinaus die soziokulturellen Realitäten der Lithiumgewinnung und beeinflussen globale Handelsmuster. Die Kontrolle der Lithiumförderung durch nur zwei Unternehmen stärkt deren Position bei der Preisbildung auf globaler Ebene und schwächt zusammen mit einem politischen System in Chile, in dem fast alle Macht vom Zentrum ausgeht, die Möglichkeiten alternativer Produktionssysteme und kritischer Stimmen gegenüber dem Modell des grünen Exraktivismus. Generell kann die hohe Nachfrage nach Lithium, die durch ein bestimmtes Narrativ über eine sozio-ökologische Transformation ausgelöst wird, die nicht nachhaltige Nutzung von Lithium fördern.
Keywords: 330